Ethylenedioxythiophene as a novel central unit for bent-core liquid crystals. Issue 12 (25th September 2016) - Gowda, Ashwath Narayana; Kumar, Sandeep
ABSTRACT: We have discovered that ethylenedioxythiophene (EDOT) can be used as a central unit for the synthesis of bent-core liquid crystals (BC LCs). Two series of EDOT-based BC LCs are prepared via Sonogashira coupling reaction. The mesophase behaviour of all the compounds was characterised using a combination of polarising optical microscopy, differential scanning calorimetry and X-ray diffraction measurements. EDOT-based three-ring compounds were found to be nonliquid crystalline, while all the four derivatives of five-ring series, including a branched alkoxy chain derivative, display enantiotropic nematic phase over wide temperature range. The bent angle of these compounds is about 153°, which falls in between typical rod-like and banana liquid crystals. The transition temperature of branched alkoxy chain compound is lower than straight alkoxy chain compounds. The detailed XRD investigations of all the mesogens corroborate the presence of nematic phase. GRAPHICAL ABSTRACT: